The COST Manual of Laboratory Animal Care and Use : Refinement, Reduction, and Research. - Howard, Bryan (CRC Press, 2016)
COST (European Cooperation in the field of Scientific and Technical Research) is an intergovernmental initiative in science and research intended to promote the coordination of nationally funded research in Europe. Four working groups discuss the housing of animals, their environmental needs, refinement of procedures, genetically modified animals, and cost-benefit analysis. Based on the activities of these working groups, this book provides the European best practices for individuals and institutions working with laboratory animals. The text also discusses the ethical evaluation of experiments and procedures involving animals.